Xirp proteins mark injured skeletal muscle in zebrafish. - Cécile Otten; Peter F van der Ven; Ilka Lewrenz; Sandeep Paul; Almut Steinhagen; Elisabeth Busch-Nentwich; Jenny Eichhorst; Burkhard Wiesner; Derek Stemple; Uwe Strähle; Dieter O Fürst; Salim Abdelilah-Seyfried (PLoS ONE)
Myocellular regeneration in vertebrates involves the proliferation of activated progenitor or dedifferentiated myogenic cells that have the potential to replenish lost tissue. In comparison little is known about cellular repair mechanisms within myocellular tissue in response to small injuries caused by biomechanical or cellular stress. Using a microarray analysis for genes upregulated upon myocellular injury, we identified zebrafish Xin-actin-binding repeat-containing protein1 (Xirp1) as a marker for wounded skeletal muscle cells. By combining laser-induced micro-injury with proliferation analyses, we found that Xirp1 and Xirp2a localize to nascent myofibrils within wounded skeletal muscle cells and that the repair of injuries does not involve cell proliferation or Pax7(+) cells. Through the use of Xirp1 and Xirp2a as markers, myocellular injury can now be detected, even though functional studies indicate that these proteins are not essential in this process. Previous work in chicken has implicated Xirps in cardiac looping morphogenesis. However, we found that zebrafish cardiac morphogenesis is normal in the absence of Xirp expression, and animals deficient for cardiac Xirp expression are adult viable. Although the functional involvement of Xirps in developmental and repair processes currently remains enigmatic, our findings demonstrate that skeletal muscle harbours a rapid, cell-proliferation-independent response to injury which has now become accessible to detailed molecular and cellular characterizations.